Untangling the type collection and recircunscription of Pseudolaelia corcovadensis: a threatened orchid species from Brazilian Atlantic Rain Forest - Wängler, Marilia S.; Meneguzzo, Thiago E. C.; van Den Berg, Cássio; Baumgratz, José Fernando A. (Phytotaxa, 2020)
Understanding the composition of the type specimen of Pseudolaelia corcovadensis is very important for establishing its taxonomic circumscription. This specimen, originally collected on the Morro do Corcovado in the municipality of Rio de Janeiro, within the Atlantic Forest biome, were mixed with those of another species of Pseudolaelia. A careful study of the specimens has made it possible to propose the lectotypification of P. corcovadensis and determine the identity of the mixed specimen, which corresponds to P. vellozicola, a similar species. The morphological description and geographical distribution, now more restricted, are presented for P. corcovadensis, and the range of P. vellozicola is established as more extensive than previously understood.